Emerging contaminant removal using eco-friendly zinc ferrite nanoparticles: Sunlight-driven degradation of tetracycline - Ramesh Vinayagam; Syonaa Batra; Gokulakrishnan Murugesan; Louella Concepta Goveas; Thivaharan Varadavenkatesan; Ashton Menezes; Raja Selvaraj (Emerging Contaminants)
Emerging contaminants, particularly pharmaceutical pollutants, pose significant environmental challenges, necessitating sustainable remediation strategies. In this study, mesoporous zinc ferrite nanoparticles (ZnFe2O4) were synthesized via a green hydrothermal method using sweet cherry leaf extract for the photocatalytic degradation of tetracycline (TC) under natural sunlight. XRD analysis confirmed a spinel cubic structure with an average crystallite size of 8.02 nm, while XPS revealed the elemental composition, including Zn (8.92 %), Fe (17.6 %), C (27.88 %), and O (45.6 %). The nanoparticles exhibited a band gap of 4.87 eV, broad UV–visible absorption, and a specific surface area of 77.99 m2/g with a mean pore size of 10.79 nm, all contributing to enhanced photocatalytic activity. VSM analysis demonstrated superparamagnetic behavior with a saturation magnetization of 10.91 emu/g, which remained stable after photocatalysis (10.81 emu/g), indicating excellent structural stability and reusability. The degradation of TC followed a first-order kinetic model, achieving 94 % efficiency in the first cycle, with the rate constant decreasing from 0.0172 min⁻1 at 10 mg/L to 0.0043 min⁻1 at 50 mg/L. Even after five cycles, the material retained over 73 % degradation efficiency, showcasing its durability. This work highlights the potential of eco-friendly ZnFe2O4 nanoparticles as a sustainable and efficient solution for mitigating emerging contaminants in wastewater, contributing to environmental remediation efforts.